2007
DOI: 10.1007/s00415-006-0385-7
|View full text |Cite
|
Sign up to set email alerts
|

Primary face motor area as the motor representation of articulation

Abstract: No clinical data have yet been presented to show that a lesion localized to the primary motor area (M1) can cause severe transient impairment of articulation, although a motor representation for articulation has been suggested to exist within M1. Here we describe three cases of patients who developed severe dysarthria, temporarily mimicking speech arrest or aphemia, due to a localized brain lesion near the left face representation of the human primary motor cortex (face-M1). Speech was slow, effortful, lacking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…31 The seed regions used for tracking the dorsal speech pathways were located immediately ventral to the hand representation in the motor cortex. In adults, lesions encompassing this cortical region are associated with severe dysarthria, 32,33 corroborating its potential crucial role for articulatory function. Importantly, the damage to the dorsal corticobulbar tract was not present at the macroscopic level, grossly measured here using track volume, because we have little evidence of frank interruption or thinning of tracks in participants with dysarthria.…”
Section: Figurementioning
confidence: 75%
“…31 The seed regions used for tracking the dorsal speech pathways were located immediately ventral to the hand representation in the motor cortex. In adults, lesions encompassing this cortical region are associated with severe dysarthria, 32,33 corroborating its potential crucial role for articulatory function. Importantly, the damage to the dorsal corticobulbar tract was not present at the macroscopic level, grossly measured here using track volume, because we have little evidence of frank interruption or thinning of tracks in participants with dysarthria.…”
Section: Figurementioning
confidence: 75%
“…To our knowledge, most previous case reports of AOS associated with lesions in the left precentral gyrus included patients diagnosed with pure AOS or AOS with mild aphasia. [12][13][14][15][16][17] Similarly, a recent lesion-overlapping study by Graff-Radford et al 22 demonstrated that the left precentral gyrus and adjacent premotor cortex were the regions of greatest overlap in 7 cases of pure AOS. In contrast, Dronkers 20 study, in which patients with both AOS and aphasia accounted for >90% of the total patients with AOS, concluded that this symptom was attributable to lesions in the brain regions outside of the precentral gyrus.…”
Section: Discussionmentioning
confidence: 95%
“…6 As each of these speech features is observed not only in AOS but also in phonemic paraphasia or dysarthria, the diagnosis of AOS is made based on specific combinations of them. 7,8 Although a considerable number of clinicoanatomic studies of AOS have been published, [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] few studies have attempted to clarify brain regions associated with AOS using neuroimaging analysis of relatively large samples. Consistent with Broca initial postulation, some of these studies concluded that AOS is attributable to lesions in the left posterior inferior frontal gyrus.…”
mentioning
confidence: 99%
“…Thus, this region may serve as a bottle-neck for speech motor output. 2 Consistently, single pulse transcranial magnetic stimulation over the presumed face-M1, either of the dominant or nondominant hemisphere or both, can delay or even temporarily abolish vocalization by reducing speech motor output. 3 Thus, theoretically, lesions either in the right or in the left face-M1 can cause disruption of commands for speech motor output, in line with the bilateral motor cortical innervation to the face, pharynx, and laryngeal muscles.…”
Section: To the Editormentioning
confidence: 98%
“…Although Itabashi et al only studied isolated nonlacunar infarcts in the left middle cerebral artery territory, most cases of aphemia were caused by left hemispheric lesions. 2 How does this laterality arise? Lotze et al reported that articulating /ka/ produces a largely asymmetrical activation centered around the lip area of the motor cortex in the left hemisphere and the entire tongue motor representation in the right hemisphere.…”
Section: To the Editormentioning
confidence: 99%